Exposure of Laboratory Animal Care Workers to Airborne Mouse and Rat Allergens - Glueck, Joshua T (American Association for Laboratory Animal Science, 2012)
Urine of rats and mice is the main source of allergenic proteins that can enter the respiratory tract of laboratory animal care workers. Little is known about the levels and determinants of these exposures in the United States. We investigated the relationship between activities in animal facilities and levels of personal exposure to allergen by collecting personal breathing zone dust samples from 7 caretakers during full workdays for 1 wk. Mice and rat urinary allergens in inhalable dust were quantified via immunoassay. The activities of the sampled workers were observed, and the methods of preventing exposure to allergens were recorded. Mouse urinary allergen was detected in 20 of 39 measurements, yielding a geometric mean of 0.8 ng/m(3) with a maximum of 24 ng/m(3). Washing and cleaning cages and the number of mice handled daily were the most important determinants of personal exposure to mouse urinary allergen, as identified by using multiple linear regressions that explained 51% of total variance. Personal exposures to mouse urinary allergen were associated with day-to-day variation of tasks rather than characteristics of workers. Where potential for personal exposure is the highest, protective measures (N95 masks and cage dumping stations) appeared to be used, as is appropriate. Rat urinary allergen was detected in 4 of 39 measurements; detectable concentrations were between 0.8 and 39 ng/m(3). Only persons who handled rats were exposed to rat urinary allergen. The current findings are valuable for establishing exposure levels against which comparisons of improvement or deterioration of personal exposures can be made.